2020
DOI: 10.1212/nxi.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to phosphatidylcholine in MS

Abstract: ObjectiveTo evaluate the value of serum immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies reactive with phosphatidylcholine (PC) and lactosylceramide (LC) as biomarkers in MS.MethodsWe developed an ultrasensitive ELISA technique to analyze serum IgG and IgM antibodies to LC and PC, which we used to analyze samples from 362 patients with MS, 10 patients with non-MS myelin diseases (Non-MSMYDs), 11 patients with nonmyelin neurologic diseases (Non-MYNDs), and 80 controls. MS serum samples included clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In addition, antibodies to sphingolipids are detected in SPMS patients and correlate with markers of disease progression such as brain atrophy, a feature of MS thought to be driven by astrocytes and microglia (Bakshi et al., 2016; Farez et al., 2009; Kanter et al., 2006). Interestingly, antibodies to sphingolipids and antibodies to other lipids are independently regulated in MS patients (Sadaba et al In press). Most importantly, sphingolipid metabolism and its products promote inflammation through multiple mechanisms (Maceyka & Spiegel, 2014).…”
Section: Sphingolipid Metabolism In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, antibodies to sphingolipids are detected in SPMS patients and correlate with markers of disease progression such as brain atrophy, a feature of MS thought to be driven by astrocytes and microglia (Bakshi et al., 2016; Farez et al., 2009; Kanter et al., 2006). Interestingly, antibodies to sphingolipids and antibodies to other lipids are independently regulated in MS patients (Sadaba et al In press). Most importantly, sphingolipid metabolism and its products promote inflammation through multiple mechanisms (Maceyka & Spiegel, 2014).…”
Section: Sphingolipid Metabolism In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Nevertheless, the incidence of the antibodies to this lipids is lower compared with that of the OIgGBs, 14,17,18,77 and these techniques are not currently used in the diagnosis of MS. 73…”
Section: Antibodies To Lipids Are a Main Characteristic Of Ms Patientsmentioning
confidence: 99%
“…Furthermore, very recently, in a large cohort study, Sádaba and colleagues examined anti-PtC IgM levels in peripheral blood of MS patients and reported these aAbs were intensely increased during CIS and RRMS. The authors suggested that serum PtC IgMs could be a candidate biomarker for the early inflammatory stages of MS [11]. Nonetheless, one should realize that anti-PtC IgMs are also present in healthy humans' serum, but they do not ligate non-oxidized forms of PtC.…”
Section: Anti-phosphatidylcholine Aabsmentioning
confidence: 99%
“…The mounting recognition that MS pathophysiology is related to neuroinflammatory processes has nourished translational and clinical research lines in the field and yielded important discoveries. For example, (1) at the translational level-the presence of autoantibodies (aAbs) against myelin or damaged neuronal derivates (compromised self-antigens; neoantigens)-was confirmed in the blood plasma and the cerebral spinal fluid (CSF) of MS patients [10,11]. Indeed, a fluctuation in these aAb levels is considered a potential biomarker for the diagnosis of MS [12,13].…”
Section: Introduction 1multiple Sclerosis and B1 Cellsmentioning
confidence: 99%